CCAL1 enhances osteoarthritis through the NF‐κB/AMPK signaling pathway. Issue 12 (24th October 2020) - Zhu, Hanzhong; Yan, Hongyu; Ma, Junan; Zhang, Hua; Zhang, Jidong; Hu, Zhiheng; Guo, Yunliang
Abstract : Osteoarthritis (OA) is a chronic joint disease characterized by articular cartilage degeneration and secondary osteogenesis. It has been previously demonstrated that the CCAL1 locus is the gene encoding tumor necrosis factor receptor superfamily member 11B ( TNFRSF11B ). The purpose of this study was to demonstrate the role of CCAL1 in OA progression and to elucidate its molecular mechanisms. We report that CCAL1 is highly expressed in the cartilage of OA patients and its expression level is positively correlated with the severity of OA. We found that CCAL1 causes a switch to the fibrosis‐prone phenotype of Human Chondrocyte‐Osteoarthritis (HC‐OA) cells. In addition, CCAL1 enhances cell viability and promotes the proliferation of HC‐OA cells. Finally, the detection of proteins associated with the NF‐κB/AMPK signaling pathway by western blot suggested that CCAL1 exerts its role on HC‐OA cells by activating the NF‐κB signaling pathway and inhibiting the AMPK signaling pathway, which was verified through the addition of NF‐κB inhibitor caffeic acid phenethyl ester (CAPE) and AMPK activator 5‐aminoimidazole‐4‐carboxamide riboside (AICAR). In summary, we report that CCAL1 may promote OA through the NF‐κB and AMPK signaling pathways. Abstract : CCAL1, a member of the tumor necrosis factor receptor superfamily 11B, encodes osteoprotegerin. We report that CCAL1 is highly expressed in osteoarthritis (OA) tissues and Human Chondrocyte‐Osteoarthritis (HC‐OA) cells and its expression level is positively correlated with the severity of OA. CCAL1 could activate NF‐κB and inhibit AMPK pathways to promote HC‐OA cell fibrosis, viability and proliferation.